2012
DOI: 10.1089/ten.tea.2011.0376
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Silk/RADA-Based Fibrous Scaffold with Triple Hierarchy for Ligament Regeneration

Abstract: While silk-based microfibrous scaffolds possess excellent mechanical properties and have been used for ligament tissue-engineering applications, the microenvironment in these scaffolds is not biomimetic. We hypothesized that coating a hybrid silk scaffold with an extracellular matrix (ECM)-like network of self-assembling peptide nanofibers would provide a biomimetic three-dimensional nanofibrous microenvironment and enhance ligament tissue regeneration after bone marrow-derived mesenchymal stem cell (BMSC)-see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The double-stranded DNA content of the samples was determined using a Quant-it PicoGreen assay (Invitrogen, Carlsbad, CA) at emission and excitation wavelengths of 485 and 528 nm, respectively, according to the manufacturer's instructions as described [10]. Total collagen content was measured with a Sircol collagen assay based on selective binding of G-X-Y amino acid sequence of collagen to Sircol dye at absorbance wavelength of 555 nm, according to manufacturer's instructions as described [16, 31]. For RNA analysis, at each time point, total cellular RNA was isolated using TRIzol (Invitrogen, Carlsbad, CA) plus RNeasy Mini-Kit (Qiagen, Valencia, CA) according to the manufacturer's instructions as described [16].…”
Section: Methodsmentioning
confidence: 99%
“…The double-stranded DNA content of the samples was determined using a Quant-it PicoGreen assay (Invitrogen, Carlsbad, CA) at emission and excitation wavelengths of 485 and 528 nm, respectively, according to the manufacturer's instructions as described [10]. Total collagen content was measured with a Sircol collagen assay based on selective binding of G-X-Y amino acid sequence of collagen to Sircol dye at absorbance wavelength of 555 nm, according to manufacturer's instructions as described [16, 31]. For RNA analysis, at each time point, total cellular RNA was isolated using TRIzol (Invitrogen, Carlsbad, CA) plus RNeasy Mini-Kit (Qiagen, Valencia, CA) according to the manufacturer's instructions as described [16].…”
Section: Methodsmentioning
confidence: 99%
“…For ligament tissue engineering, usage of various materials including silk, polytetrafluoroethylene, poly(lactic-coglycolic acid) and PLLA has been reported [18][19][20][21][22]. Ideally, scaffolds should have good mechanical strength during the early stages, which it can adequately maintain during tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Ligament injuries affect millions worldwide and current treatment often involves the use of allografts which have been associated with serious complications such as ligament laxity, donor site morbidity, and inflammatory response. Chen et al fabricated a composite material which consisted of a silk‐based microfibrous scaffold, which possesses good mechanical properties, coated with the Ac‐(RADA) 4 ‐CONH 2 self‐assembling peptide hydrogel which provides an ECM‐like network of peptide nanofibers . The authors seeded this composite material with BMSCs and observed that compared with the uncoated control, the peptide‐coated scaffolds showed enhanced BMSC proliferation, metabolism, and fibroblastic differentiation during 3 weeks of culture.…”
Section: Applications Of Self‐assembling Peptide Hydrogels In Tissue mentioning
confidence: 99%
“…Chen et al fabricated a composite material which consisted of a silk-based microfibrous scaffold, which possesses good mechanical properties, coated with the Ac-(RADA) 4 -CONH 2 self-assembling peptide hydrogel which provides an ECMlike network of peptide nanofibers. 48 The authors seeded this composite material with BMSCs and observed that compared with the uncoated control, the peptide-coated scaffolds showed enhanced BMSC proliferation, metabolism, and fibroblastic differentiation during 3 weeks of culture. Furthermore, BMSC-seeded, peptide-coated scaffolds showed increased temporal expression of key fibroblastic ECM proteins including collagen type I and III, tenascin-C, and glycosaminoglycan, and possessed 7% higher maximum tensile load compared with the controls.…”
Section: Ligament Regenerationmentioning
confidence: 99%